Can we provide quality #MedEd on social media?. Issue 12 (December 2022) - Lowe-Calverley, Emily; Barton, Matthew; Todorovic, Michael
Abstract : In 2020, universities shut their doors and educators uploaded educational content onto online learning management systems. Two years later, students and academics are returning to campus, but many have decided to maintain the delivery of online classes. Now, with education firmly situated online, the focus has transitioned to identifying best practice, refining online delivery, and considering nontraditional platforms. Here, we highlight how social media can provide accessible, quality medical education experiences.